2016
DOI: 10.1111/1471-0528.13910
|View full text |Cite
|
Sign up to set email alerts
|

Donor oocyte conception and pregnancy complications: a systematic review and meta‐analysis

Abstract: Background Observational studies showed that women with a donor oocyte (DO) pregnancy have an increased risk of pregnancy complications.Objectives Systematic review and meta-analysis to compare pregnancy complications of DO pregnancy with autologous oocyte in vitro fertilisation (IVF), and whether DO pregnancy acts as an independent risk factor.Search strategy Online searches of databases from 1 January 1980 to 31 January 2015 were performed using a set of relevant keywords.Selection criteria All studies compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 49 publications
(158 reference statements)
0
47
0
1
Order By: Relevance
“…Very interesting data from sub-analysis demonstrated that in donor cycles the incidence of LBW was increased in PTB (RR 1.24, 95 % CI 1.19 to 1.29) but decreased (RR 0.86, 95 % CI 0.8 to 0.93) in term deliveries. The third meta-analysis included 11 observational studies for a total of 81,752 cycles comparing obstetric complications of pregnancies achieved after OD and autologous oocyte, and controlled for specific ART procedure (IVF or ICSI) [153]. In OD pregnancies the risk of developing PIH/PE, considered the primary endpoint, was significantly higher (OR 3.92, 95 % CI 3.21 to 4.78) also after sub-analysis for singleton (OR 2.90, 95 % CI 1.98 to 4.24) and twin (OR 3.69, 95 % CI 2.62 to 5.19) pregnancies [153].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Very interesting data from sub-analysis demonstrated that in donor cycles the incidence of LBW was increased in PTB (RR 1.24, 95 % CI 1.19 to 1.29) but decreased (RR 0.86, 95 % CI 0.8 to 0.93) in term deliveries. The third meta-analysis included 11 observational studies for a total of 81,752 cycles comparing obstetric complications of pregnancies achieved after OD and autologous oocyte, and controlled for specific ART procedure (IVF or ICSI) [153]. In OD pregnancies the risk of developing PIH/PE, considered the primary endpoint, was significantly higher (OR 3.92, 95 % CI 3.21 to 4.78) also after sub-analysis for singleton (OR 2.90, 95 % CI 1.98 to 4.24) and twin (OR 3.69, 95 % CI 2.62 to 5.19) pregnancies [153].…”
Section: Resultsmentioning
confidence: 99%
“…The third meta-analysis included 11 observational studies for a total of 81,752 cycles comparing obstetric complications of pregnancies achieved after OD and autologous oocyte, and controlled for specific ART procedure (IVF or ICSI) [153]. In OD pregnancies the risk of developing PIH/PE, considered the primary endpoint, was significantly higher (OR 3.92, 95 % CI 3.21 to 4.78) also after sub-analysis for singleton (OR 2.90, 95 % CI 1.98 to 4.24) and twin (OR 3.69, 95 % CI 2.62 to 5.19) pregnancies [153]. Also the odds for SGA (OR 1.81, 95 % CI 1.26 to 2.60), PTB (OR 1.34, 95 % CI 1.08 to 1.66), and caesarean section (OR 2.71, 95 % CI 2.23 to 3.30) were increased [153].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HPA data of parents should be obtained in case another pregnancy is planned, as the findings may affect future choices of a different gestational mother or oocyte donor. Performing HPA typing for the surrogate mother, oocyte donor, and father in all such contemplated pregnancies should be considered since pregnancy complications, and probably FNAIT as well, are more common in oocyte donor pregnancies …”
Section: Discussionmentioning
confidence: 99%